Pengaruh Video Animasi Terhadap Pengetahuan Proses Fotosintesis Pada Siswa Kelas IV SD - Sofyan Iskandar; Primanita Sholihah Rosmana; Anggy Deviyanti; Asbarina Aghna Qolby; Luthfiannisa Ghessiani; Ranisa Devi (Peneliti.net, 2023)
The process of photosynthesis is one of the material in science subjects that is taught to fourth grade elementary school students, where students are expected to be able to identify and understand the process of photosynthesis in plants. Along with the times and advances in digital technology as it is today, the world of education has begun to adapt and apply technological developments as educational tools. One of them is by developing conventional learning media into ICT-based learning media such as animated videos. The purpose of this study was to find out whether there was an effect of applying animated videos as learning media in the photosynthesis process material in Class IV SDN 1 Citalang, Purwakarta. The method used in this study is a quantitative method using pre-experiments, which only includes one class given pre and post tests. Based on the result of the research conducted, it showed an increase in student’s knowledge about the proscess of photosynthesis. This can be seen from the results of the pretest data with an average value of 58,8 and posttest with an average value 72. So it can be concluded that there is an effect of video animation on photosynthesis process knowledge of fourth grade elementary school student.